Internet of Things: A survey on the security of IoT frameworks. (February 2018) - Ammar, Mahmoud; Russello, Giovanni; Crispo, Bruno
Highlights: Giving a high overview of the current state of the art IoT platforms. Providing a high level comparison between the different security architectures of the various frameworks. Focusing on the models designed and approaches developed for ensuring security and privacy in these frameworks. Illustrating the pros and cons of each framework in terms of fulfilling the security requirements and meeting the standard guidelines. Exploring the design flaws and opening the door for more in depth security analysis against potential threats. Abstract: The Internet of Things (IoT) is heavily affecting our daily lives in many domains, ranging from tiny wearable devices to large industrial systems. Consequently, a wide variety of IoT applications have been developed and deployed using different IoT frameworks. An IoT framework is a set of guiding rules, protocols, and standards which simplify the implementation of IoT applications. The success of these applications mainly depends on the ecosystem characteristics of the IoT framework, with the emphasis on the security mechanisms employed in it, where issues related to security and privacy are pivotal. In this paper, we survey the security of the main IoT frameworks, a total of 8 frameworks are considered. For each framework, we clarify the proposed architecture, the essentials of developing third-party smart apps, the compatible hardware, and the security features. Comparing security architectures shows that the same standards used for securing communications, whereas different methodologies followed for providing other security properties.